Ensemble experiment to investigate Antarctic meltwater input under global warming by GFDL CM2.1 - Shin, Yechul (Zenodo, 2023)
Dataset for "Non-monotonic responses of Atlantic Meridional Overturning Circulation to Antarctic meltwater forcing" submitted to GRL. GW indicates global_warming experiments without meltwater input whereas MW is with meltwater input. atlantic, global, surface_density, integrated_density.mat is preprocessed ocean dataset (structure) by MATLAB.